PENGEMBANGAN FASILITAS PAUD KUSUMA HARAPAN, DUSUN PEKARANGAN, DESA BATURITI, TABANAN BALI - Nyoman Sri Rahayu (Jurnal Lentera Widya, 2023)
Community Service activities are organized by the Department of Interior Design, Bali Institute of Design and Business, in the form of activities for the Development of Kusuma Harapan PAUD facilities. This activity is located in the hamlet of Pekarangan, Baturiti Village, Tabanan Bali. At the community service this time, the classroom interior was arranged, furniture painted, wall painting and a mural design with an ocean theme. The methods used include initial observations reviewing the location and observing the interior conditions of the room. Next is design planning. Implementation in the field, students and lecturers began cleaning the wall area and the process of sanding the wall, followed by priming the wall, and making sketches on the wall. Then the next day it was continued with coloring and finishing the mural using paint. Monitoring and evaluation is carried out by lecturers. Guidance and direction are given to get maximum results Implementation in the field, students and lecturers began to coordinate with teachers regarding the space to be repaired. Wall area cleaning and wall sanding process. Followed by basic wall paint, and sketched on the wall. Then the next day proceed with coloring and finishing using paint. This activity was carried out by students and lecturers of the IDB Bali Interior Design Department. Keyword : Development, Facilities, interior.